2020
DOI: 10.1002/ange.201915762
|View full text |Cite
|
Sign up to set email alerts
|

Multiphotonen‐Anregung in der Photoredoxkatalyse: Konzepte, Anwendungen und Methoden

Abstract: Die Energie sichtbarer Photonen und die zugänglichen Redoxpotentiale üblicher Photokatalysatoren schränken die Anzahl derjenigen Photoreaktionen ein, die durch sichtbares Licht angetrieben werden können. Da UV‐Anregung schädlich ist und häufig Nebenreaktionen auslöst, ist sichtbares Licht oder sogar NIR‐Strahlung vorzuziehen. Die Photochemie befasst sich momentan mit einer zweischneidigen Herausforderung, und zwar mit dem Wunsch, immer thermodynamisch anspruchsvollere Reaktionen mit immer kleineren Photonenene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 174 publications
0
12
0
1
Order By: Relevance
“…However, catalytic species of a much higher reducing power can be generated via the reductive quenching of the catalyst followed by the subsequent excitation with a second visiblelight-photon. 30,[32][33][34] Although the typically used reductive quenchers include tertiary amines, Hantzsch esters, alcohols, ascorbate anions etc., 35 it has recently been shown that the efficient quenching of excited Ir-complexes can also be achieved using simple halide anions, leading to Ir(II)-species and halide radicals. [36][37][38][39][40] We decided to test, if Branions, which are released upon the single-electron-reduction and fragmentation of alkyl bromides, can be recycled and used as mediators in the Minisci reaction -quench the excited Ir(III)-photocatalyst and thus promote the generation of alkyl radicals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, catalytic species of a much higher reducing power can be generated via the reductive quenching of the catalyst followed by the subsequent excitation with a second visiblelight-photon. 30,[32][33][34] Although the typically used reductive quenchers include tertiary amines, Hantzsch esters, alcohols, ascorbate anions etc., 35 it has recently been shown that the efficient quenching of excited Ir-complexes can also be achieved using simple halide anions, leading to Ir(II)-species and halide radicals. [36][37][38][39][40] We decided to test, if Branions, which are released upon the single-electron-reduction and fragmentation of alkyl bromides, can be recycled and used as mediators in the Minisci reaction -quench the excited Ir(III)-photocatalyst and thus promote the generation of alkyl radicals.…”
Section: Resultsmentioning
confidence: 99%
“…The latter species can undergo consecutive absorption of a second photon, resulting in the formation of a strongly reducing form of the iridiumcomplex 30,32 or a solvated electron. 34 SET to alkyl bromide A followed by fragmentation affords alkyl radical B and a bromide anion, which participates in subsequent catalytic cycles. An addition of alkyl radical B to pyridinium salt C provides the radical cation D, able to undergo hydrogen-atom-transfer (HAT) with electrophilic bromine radical.…”
Section: Resultsmentioning
confidence: 99%
“…In 2021, the Wenger group published a thorough investigation of the mechanism behind the hydrodehalogenation of selected aryl halides through sensitization-induced electron transfer (Scheme 31 ). 63 fac -Ir(ppy) 3 was applied as a photosensitizer, 2,7-di- tert -butylpyrene ( t BuPyr) as annihilator and N , N -dimethylaniline (DMA) as terminal reductant. They confirmed an sTTA-UC mechanism where the triplet 3 fac -Ir(ppy) 3 * catalyst performs a TTEnT towards t BuPyr resulting in the formation of 3 t BuPyr*.…”
Section: Emerging Techniquesmentioning
confidence: 99%
“…ConPET and related e-PRC strategies allow the formation of excited radical anions/cations that possess exceptional redox potentials. 63 Although it unlocks the photocatalytic activation of conventionally unreactive substrates using a single catalyst, the excited radical species is often very short-lived. For this reason, bimolecular quenching usually requires high quencher concentrations or the presence of ground-state pre-aggregates.…”
Section: Emerging Techniquesmentioning
confidence: 99%
“…PRC reactions are limited by the redox window of photocatalysts, which is in most part defined by the energy of visible photons (ca. 1.8–3.1 eV) [3] . UV photons that access higher energy limits come with penalties of less energy‐ and cost‐efficient reactors, safety and the direct excitation of substrate molecules leading to deleterious pathways.…”
Section: Introductionmentioning
confidence: 99%